Psychosocial implementation of the community in the christian religious education praxis of Dayak Ngaju family - Wainarisi, Yane Octavia Rismawati (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
Every tribe has a unique way of passing their culture to their descendants. So do Dayak Ngaju Tribe. Dayak Ngaju is the name of the most extraordinary tribe in Center Borneo. In the past, they live within people groups in Huma Betang. Huma Betang is the name of Dayak Ngaju Houses at once but as a philosophy of Dayak Ngaju.  Huma Betang contains 100 - 150 people and is an extraordinary place for Dayak Ngaju people because they do all their social activities as a family and as a part of society in this place. Elderly people in Huma Betang teach their Children about culture or tradition, beliefs, norms, etc in Huma Betang. This fact gives ample opportunity for Christian Education since Christianity became the majority religion in Dayak Ngaju to teach the Dayak Ngaju People Group about faith in Christ. This article uses the qualitative descriptive method to describe how Dayak Ngaju people's psychosocial condition can give them a big opportunity to implement Christian education in their families, especially in the Huma Betang context. This research can help in developing an appropriate psychosocial approach model for implementing Christian religious education among Ngaju Dayak families. This involves understanding how individual and group psychology in Ngaju Dayak society influences the acceptance and effectiveness of Christian religious education.